Cytotoxic, apoptotic, and genetic evaluations of Nigella sativa essential oil nanoemulsion against human hepatocellular carcinoma cell lines - Ahmed A. Abd-Rabou (BMC, 2021)
Abstract Background Phytochemicals and plant extracts are showing promising anticancer potentials. In the current study, the volatile faction (essential oil) of Nigella sativa seeds was evaluated against some hepatocellular carcinoma (HCC). The essential oil was extracted and characterized by chromatographic techniques to reveal its chemical composition, especially thymoquinone. Then, the oil was fabricated in two nanoemulsion formulations (F1 and F2), which differ in their composition of surfactants. The cytotoxicity and apoptotic activities of the essential oil and its nanoemulsions were evaluated in vitro against HepG2 and Huh-7 cell lines. Normal WI-38 cell line was also included in that evaluation to study the selectivity and safety of the different formulations on normal cells. Results Gas chromatographic analysis indicated that the essential oil is composed mainly of p-cymene (40.0%), thymoquinone (31.2%) and trans-α-thujene (12.8%). Particle size of the nanoemulsions ranged between 9.4 and 119.7 nm depending on the type of surfactant used in the formulation process. The pure essential oil and its two nanoemulsions (F1 and F2) showed dose-dependent antiproliferative activity against both HCC cells. This activity reached its highest cell inhibition in the case of nanoemulsion (F2) where the proliferation percentage was only 21.9% and 9.2% against HepG2 and Huh-7 cells, respectively. The same nanoemulsion (F2) also showed the lowest IC50 values (55.7 and 35.5 µg/ml) against both HepG2 and Huh-7 cells, respectively, compared to 100 µg/ml for the reference drug Doxorubicin. Flow cytometric analysis also confirmed that nanoemulsion (F2) has the highest apoptotic activity compared to nanoemulsion (F1) and the pure unformulated essential oil. Genetic expressions of pro-apoptotic (Bax) and the anti-apoptotic (Bcl-2) gene markers evaluation revealed that nanoemulsion (F2) has better activity in upregulating (Bax) and down-regulate (Bcl-2) with the highest Bax/Bcl-2 ratio (69) was found against Huh-7 cells. All N. sativa nanoemulsions showed minimal cytotoxicity on the normal WI-38 cell, indicating wide safety margins due to selective properties. Conclusion Overall, the study revealed the potentials of N. sativa essential oil, after formulation in specially tailored nanoemulsion for application as potential adjuvant liver anticancer agent. Graphical Abstract